2023
DOI: 10.1021/acs.est.3c00719
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acids as Potential Precursors to Odorous Compounds in Tap Water during Spring Runoff Events

Abstract: The onset of spring runoff in northern climates and tap water odor events are difficult to predict because common water quality parameters cannot fully explain the intermittent odor events that occurred over past decades. Studies have shown that small polar water-soluble compounds, such as amino acids (AAs), leach first from ice/snowmelt. AAs are known to produce odorous compounds, such as aldehydes and chloroaldimines, upon chlorination. Therefore, we proposed that AAs may serve as markers for small and solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In another study, Craven et al solved a years-long mystery as to what chemicals were causing taste and odor events in Edmonton's drinking water following spring runoff (from melting snow). 104 These taste-and-odor events could not be explained by the commonly occurring geosmin or methylisoborneol, algal metabolites that plague most drinking water plants around the world. Instead, the authors found high amino acid levels following these spring runoff events (increasing from <100 ng/L to 5500 ng/L), accompanied by taste-and-odor complaints.…”
mentioning
confidence: 99%
“…In another study, Craven et al solved a years-long mystery as to what chemicals were causing taste and odor events in Edmonton's drinking water following spring runoff (from melting snow). 104 These taste-and-odor events could not be explained by the commonly occurring geosmin or methylisoborneol, algal metabolites that plague most drinking water plants around the world. Instead, the authors found high amino acid levels following these spring runoff events (increasing from <100 ng/L to 5500 ng/L), accompanied by taste-and-odor complaints.…”
mentioning
confidence: 99%